KEMAMPUAN PESERTA DIDIK MENULIS TEKS BERITA KELAS VII SMP NEGERI 26 PONTIANAK - Ramadhanty, Annisa; Wartiningsih, Agus; Muzammil, Ahmad Rabi’ul (Universitas Tanjungpura, 2025)
This research aims to analyze the writing ability of news texts of seventhgrade students at SMP Negeri 26 Pontianak. The method used is descriptive to describe the students' ability in writing news texts, with a qualitative research approach. The subjects of this research are the seventh-grade students of class VII B at SMP Negeri 26 Pontianak, totaling 31 students. The data obtained are the results of students' writing abilities in creating news texts in terms of structure and language rules. The results of the analysis of writing abilities in the aspect of text structure show that 7 students have excellent abilities, 12 students have abilities in the good category, 11 students have abilities in the fair category, and 1 student has abilities in the very poor category. Furthermore, the results of the analysis of news text abilities in terms of structure show that there are 3 students with abilities in the poor category and 28 students with abilities in the very poor category.